Tinjauan Yuridis Terhadap Pengaturan Pemberhentian Notaris Dalam Konteks Kepailitan - Ni Kadek Winda Nandayani; I Gede Putra Ariana (Fakultas Hukum, Universitas Warmadewa, 2024)
The stipulations of Bankruptcy Regulation under Law Number 2 of 2014, specifically in Article 12 letter a, which pertains to the Notary Position, engender a variety of interpretations. According to this provision, a Notary who is adjudicated bankrupt by judicial decree faces dishonorable discharge. Such dismissal contravenes the established bankruptcy principles outlined in Law Number 37 of 2004 on Bankruptcy. The objective of this research is to explore the foundational legal framework governing the termination of a Notary's role and to examine the legal ramifications associated with such dismissal within the framework of bankruptcy. This investigation adopts a normative legal research methodology, motivated by the unclear legal norms present. Legal documents serve as both the primary research tool and the primary source of data for identifying issues. The findings reveal that the ambiguity engendered by Article 12(a) of the Notary Position Law, which governs the dishonorable dismissal of notaries declared bankrupt, raises questions about whether notaries should be considered as debtors or as representatives of their official capacities. This ambiguity contributes to legal uncertainty and the possibility of injustice. The bankruptcy notary loses the authority to take care of his personal property and the right to make authentic deeds, although he can still perform other legal acts. Violations in bankruptcy can cause the deed to lose its authenticity, and the aggrieved party can seek compensation. The Notary Office Law has not regulated the details of Notary bankruptcy, including document security and reappointment, causing ambiguity in norms.